The partial fraction expansion takes the form
-6x/((x + 2) (x + 8)) = a/(x + 2) + b/(x + 8)
Both factors in the denominator are linear, so the numerators in the corresponding partial fractions have degree 1 - 1 = 0 and are thus constants.
Combine the fractions on the right side into one with a common denominator, then set the numerators on both sides of the equation equal to each other:
-6x = a (x + 8) + b (x + 2)
Expand the right side and collect terms by powers of x :
-6x = (a + b) x + (8a + 2b)
It follows that
a + b = -6 and 8a + 2b = 0
==> a = -2 and b = 8
So we end up with
-6x/((x + 2) (x + 8)) = -2/(x + 2) + 8/(x + 8)